The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5455/vetworld.2013.185-188
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial sensitivity and resistance of Salmonella Enteritidis isolated from natural samples

Abstract: Aim: To test the sensitivity of S. Enteritidis for selected antibiotics. Materials and Methods: S. Enteritidis isolates obtained from different samples of chicken, mutton, turkey meat, faecal and cloacal samples of poultry and turkey, eggs, water and feed were subjected for sensitivity and resistance to selected antibiotics like- Chloramphenicol (30μg), Gentamicin (10 μg), Nalidixic Acid (30 μg), Tetracycline (30 μg), Ciprofloxacin (5 μg), Amikacin (30 μg),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Shah and Kojero (2012) also found resistance against nalidixic acid. The sensitivity of isolates to chloremophenicol, amikacin in the present study was accord to the report of (Putturu et al, 2013).…”
Section: Int J Biosci 2017supporting
confidence: 91%
See 1 more Smart Citation
“…Shah and Kojero (2012) also found resistance against nalidixic acid. The sensitivity of isolates to chloremophenicol, amikacin in the present study was accord to the report of (Putturu et al, 2013).…”
Section: Int J Biosci 2017supporting
confidence: 91%
“…There is a significant need of epidemiological surveillance of antimicrobial susceptibility to identify the alteration in resistance at different levels on regular basis (Putturu et al, 2013).…”
Section: Int J Biosci 2017mentioning
confidence: 99%
“…In contrast to our study, Ramya et al showed that the susceptibility of Salmonella spp. for ciprofloxacin and amoxicillin were 100% and 82%, respectively ( 43 ). Furthermore, studies in geographical areas such as Bangladesh have also shown approximately 50% resistance to five antibiotics among 16 Salmonella spps.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal samples were collected by sterile swab and placed in a falcon tube (15 ml) containing buffered peptone water (Oxoid, Basingstoke, Hampshire, UK) for Salmonella spp. ( 36 ) and Mueller-Hinton broth for Staphylococcus spp. ( 37 ).…”
Section: Methodsmentioning
confidence: 99%